PENANGANAN PASCA WABAH COVID-19 MELALUI PENINGKATAN SARANA KEBERSIHAN DI SEKOLAH DASAR - Isdawimah; Nadhiroh, Nuha; Tabrany, Susilawati (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2021)
Abstract The resilience of a country is determined by the level of health of its citizens. The COVID-19 outbreak has ravaged the world. This virus outbreak is expected to subside in May 2020. One of the causes of the spread of this virus is poor hygiene lifestyle. One of the problems related to health at Kukusan Elementary School is the unavailability of a place to wash hands. Therefore, it is necessary to prepare facilities for students to maintain personal hygiene and the environment, so that virus attacks do not occur again. The experience of children from an early age in maintaining personal and environmental hygiene is intended so that later they will always live clean wherever they are. One of the effective efforts to improve student health as well as educate students to get used to living clean is by providing cleanliness facilities that are easy to use, and are closely related to their daily activities. The hope is that this activity can instill the mindset of students so that they can maintain cleanliness independently wherever they are, increase student teacher and employee awareness of personal and environmental hygiene, so that it has an impact on improving their health, making it easier for teachers to teach and give examples of how to live clean and how to keep the environment clean. , opening up the knowledge of teachers and employees about how to use, maintain and repair cleaning facilities, and increase public interest in schools because the school facilities are complete. Keywords—COVID-19, early years, hygiene, health Abstrak Ketahanan negara ditentukan oleh tingkat kesehatan warganya. Wabah COVID-19 telah memporakporandakan dunia. Wabah virus ini diperkirakan mereda pada bulan Mei 2020. Salah satu penyebab penyebaran virus ini adalah gaya hidup yang kurang bersih. Salah satu masalah yang terkait dengan kesehatan di sekolah SDN Kukusan adalah belum tersedianya tempat cuci tangan. Karena itu, perlu dipersiapkan sarana bagi para siswa untuk menjaga kebersihan diri dan lingkungan, agar serangan virus tidak terjadi lagi. Pengalaman anak sejak dini menjaga kebersihan diri dan lingkungan ini dimaksudkan agar kelak mereka senantiasa hidup bersih dimanapun mereka berada. Salah satu upaya efektif meningkatkan kesehatan siswa sekaligus mendidik siswa agar terbiasa hidup bersih adalah dengan memberikan sarana kebersihan yang mudah digunakan, dan erat hubungannya dengan kegiatan mereka sehari-hari. Harapannya kegiatan ini dapat menanamkan mindset siswa agar dapat menjaga kebersihan secara mandiri dimanapun mereka berada, meningkatkan kepedulian siswa guru dan karyawan terhadap kebersihan diri dan lingkungan, sehingga berdampak pada peningkatan kesehatan mereka, memudahkan guru mengajarkan dan memberi contoh cara hidup bersih dan cara menjaga kebersihan lingkungan, membuka wawasan guru dan karyawan tentang cara pemanfaatan, perawatan dan perbaikan sarana kebersihan, dan meningkatkan animo masyarakat terhadap sekolah karena fasilitas sekolahnya lengkap. Kata kunci— COVID-19, kebersihan, kesehatan, usia dini